UI/UX Implementation for Junior High Adventure Game using UCD Method in P5 Project - Deuis Nur Astrida; M. Syaiful Amin; Arifudin, Dani (ACSIT, 2024)
One of the activities in the independent learning curriculum is thePancasila Student Profile Strengthening Project (P5), a project-basedco-curricular activity aimed at enhancing competence and characteraccording to the Pancasila learner profile, based on GraduationCompetency Standards. One theme of the P5 project is engineeringand technology, where students create innovative works usingtechnology to solve problems in their educational environment, suchas environmental pollution and limited educational resources. Anexample outcome is the adventure game